Peran Locus Of Control Dalam Hubungan Job Insecurity Dengan Komitmen Organisasi Dan Kepuasan Kerja - noviarini, ni made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; Volume.02.No.12.Tahun 2013, 2013)
This study aims to determine the role of locus of control in relation to job insecurity and organizational commitment and job satisfaction. The samples in this study were 101 employees of PLN (State-owned Power Company) consists of permanent employees and outsourced employees. Data analysis technique used is based on analysis of General Linear Model (GLM) with a Univariate Varian Analysis (ANAVA) Results of this study indicate that there is no influence of job insecurity on organizational commitment and job satisfaction of employees. However, when entering the role of locus of control in relation job insecurity with organizational commitment and employee satisfaction then the group of employees with an external locus of control in an environment of high job insecurity has a commitment with the lowest job satisfaction, compared to employees who have an internal locus of control Implications of the findings in this study are that the company continues to conduct response actions on the importance of job insecurity in employment of employees. It is necessary to carry out trainings more frequently to improve self-esteem of employees so that each employee is confident of his/her ability to work. Involving employees in making decisions will make employees feel as a part of the company. Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4
Keywords: id